GAMBARAN ALASAN PEMILIHAN TERAPI BEKAM DI RUMAH SEHAT ISLAMIC NURSE KOTA PEKANBARU - Efprita Meiga Diah Sari; Sri Wahyuni; Darwin Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Cupping is one of the alternative treatments that are in great demand by the public. Cupping therapy is useful for treating many diseases, especially diseases related to blood circulation such as hypertension, diabetes, varicose veins, cholesterol and others. In addition, cupping therapy can also maintain a healthy body. The factors that influence people in choosing alternative cupping treatment are economic factors, cultural factors, psychological factors, community personal factors, social factors, and knowledge factors. Objective: Knowing the description of the reasons for choosing cupping therapy at the Islamic Nurse Health House Pekanbaru City. Method: the method used is descriptive quantitative. Sample: the sample in this study were patients who came to do cupping therapy at the Islamic Nurse Health House as many as 50 people who were selected by accidental sampling technique.. Results: the results showed that most of the respondents were in the early elderly (46-55 years) as many as 15 people (30%), female as many as 26 people (52%), having a job as an entrepreneur as many as 16 people (32%) were Muslim. as many as 50 people (100%), have high knowledge as many as 40 people (80%), high motivation as many as 30 people (60%), and technology and information sources that do not support as many as 25 people (50%).Conclusion: The reason people choose cupping therapy is influenced by high knowledge, high motivation and supporting information technology. Keyword: Cupping therapy, information technology, knowledge, motivation